The Effect of Service Quality on Domestic Tourist Satisfaction at Sanur - Nusa Lembongan Sea Transportation: A Case Study at D'camel Fast Boat - Ni Luh Gede Pande Radyanti; Nyoman Reni Ariasri; Made Darmiati (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
Studies on tourists’ satisfaction have been an area of interest for many scholars, however, the satisfaction of tourists visiting Nusa Lembongan, Bali by fast boat has not been given attention. This study, therefore, aimed to investigate the effect of the service quality of D’Camel Fast Ferry on domestic travelers’ satisfaction. Using five dimensions of service quality, which are reliability, responsiveness, assurance, empathy, and tangible and using simple regression technique analysis with SPSS 23 device. There were 100 respondents in this research, using Purposive Sampling as the sampling technique. The data was collected by using interviews and questionnaires. The result of the research showed that the quality service of D’Camel Fast Boat influence 50,2% of satisfaction among domestic travelers. The results showed that the service quality level is good, and the satisfaction level of domestic travelers is good. The service quality of D’Camel Fast Boat must be increased so travelers could feel satisfied with the service given.